An Insight to the Composition of Pre-Hispanic Mayan Funerary Pigments by 1H-NMR Analysis - Kadwin J. Pérez-López; Vera Tiesler; Patricia Quintana; Emanuel Hernández-Nuñez; Gloria I. Hernández-Bolio (Molecules, 2021)
The funerary rites of particular members of the pre-Hispanic Mayan society included the pigmentation of the corpse with a red color. In order to understand this ritual, it is first necessary to identify the constituents of the pigment mixture and then, based on its properties, analyze the possible form and moment of application. In the present approach, 1H-NMR analysis was carried to detect organic components in the funerary pigments of Xcambó, a small Maya settlement in the Yucatan Peninsula. The comparison of the spectra belonging to the pigment found in the bone remains of seven individuals, and those from natural materials, led to the identification of beeswax and an abietane resin as constituents of the pigment, thus conferring it agglutinant and aromatic properties, respectively. The 1H-NMR analysis also allowed to rule out the presence of copal, a resin found in the pigment cover from paramount chiefs from the Mayan society. Additionally, a protocol for the extraction of the organic fraction from the bone segment without visible signs of analysis was developed, thus broadening the techniques available to investigate these valuable samples.